Approach for the analysis of TES technologies aiming towards a circular economy: Case study of building-like cubicles. (May 2020) - Boer, Dieter; Segarra, Mercè; Fernández, A. Inés; Vallès, Manel; Mateu, Carles; Cabeza, Luisa F.
Abstract: The objective of this study is to establish an initial framework to evaluate and improve the sustainability of technologies integrating thermal energy storage to come closer to a circular economy. This is applied to a case study for a building-like cubicle that includes different options of phase change materials. For the construction of a cubicle, materials can come from ores and virgin or recycled feedstock. In order to decrease the impact of materials and approach to a circular economy, the recycled content of materials at the start of life should be as high as possible. This recycled fraction in current supply depends on the available technologies for reintroducing the recycled materials in the production processes, together with virgin materials coming from primary sources. The results of the analysis show that the decrease of the environmental impact of recycling at the end of life is lower than 5%, while using recycled materials replacing virgin raw materials could reduce the overall impact by up to 30%. Most relevant materials are bricks, steel, and aluminum. Thus, reuse and recycling of materials and components must be integrated into the initial design in order to come closer to the concept of circular economy. Graphical abstract: Image 103291686 Highlights: Scenarios consider virgin feedstock and different degrees of recycling. Use of recycled materials has highest potential of impact reduction. The environmental impact could be reduced by 30%. Need of new processes and product including concepts of circular economy.